A fully ceramic coated fuel and preparation method thereof
Through gel injection molding and sintering processes, the density and complex structure preparation problems of full ceramic coated dispersed fuel are solved, and the full ceramic coated fuel with high density and high thermal conductivity is achieved. It is suitable for high-temperature reactors and simplifies production Process and reduce costs.
Patent Information
- Application Number
- CN202210736494.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-06-27
AI Technical Summary
现有技术难以制备结构复杂的全陶瓷包覆弥散燃料,致密化困难,基体致密度低,无法满足高温反应堆的设计需求。
Using gel injection molding and sintering technology, high-density full ceramic coating is prepared by optimizing the content of diffused fuel particles in the mixed powder, ball milling mixing, sintering additive addition, gel film injection process and high-temperature sintering treatment. fuel.
Near-net molding of complex-shaped ceramic fuels is achieved, the density, thermal conductivity and toughness of fuel elements are improved, the application needs of high-temperature reactors are met, the production process is simplified, and the costs are reduced.
Smart Images

Figure CN115050499B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of dispersed fuels, in particular to the field of molding and preparation of ceramic fuels, and more particularly to fully ceramic-coated dispersed fuels used in nuclear reactors and a preparation method thereof. Background Art
[0002] Improving the fuel's ability to contain fission products and fuel integrity is an important way to improve reactor safety. The existing UO2 fuel pellets have poor fission product containment, are prone to cracking under normal operating temperature gradients, and have atypical interactions with cladding materials, causing fuel rod damage and radioactive material leakage. After the Fukushima nuclear accident, the international nuclear fuel field proposed a nuclear power fuel development direction with the goal of improving the ability of nuclear fuel to maintain structural integrity in harsh environments.
[0003] In order to improve the fission product containment capacity of fuel, all-ceramic coated dispersed fuel has been designed internationally. It is a fuel particle (TRISO particle) formed by coating a multilayer structure of loose pyrolytic carbon, dense pyrolytic carbon (IPyC, OPyC), SiC, etc. on the surface of the fuel core, and then dispersed in the external SiC matrix to finally form a fully ceramic coated dispersed fuel. Compared with traditional UO2 ceramic fuel, the fully ceramic coated dispersed fuel has the following characteristics: First, high thermal conductivity. After irradiation, the thermal conductivity of the fully ceramic coated dispersed fuel can still reach twice that of UO2 fuel. Second, good fracture toughness, the core block has good crack resistance. The SiC matrix has high fracture toughness and can effectively prevent crack propagation. Third, excellent fission product containment capacity. The multiple coating structures and SiC matrix materials effectively prevent the release of radioactive fission products. Fourth, excellent irradiation stability. The SiC matrix material has strong resistance to radiation swelling, and the fully ceramic coated dispersed fuel has small irradiation deformation.
[0004] In addition, due to the excellent properties of SiC matrix materials in all-ceramic coated dispersed fuel, such as excellent high-temperature oxidation resistance, ablation resistance, high melting point and high high-temperature strength, the SiC matrix has the characteristics of both cladding and structural materials, which makes all-ceramic coated dispersed fuel have broad application prospects in ultra-high temperature reactors. Ultra-high temperature reactors require all-ceramic coated dispersed fuel pellets with complex structures, high TRISO particle content and high matrix density. Summary of the invention
[0005] The technical problem to be solved by the present invention is that the current method for preparing dispersion fuel is not suitable for preparing all-ceramic coated dispersion fuel with complex structure. The present invention provides a all-ceramic coated fuel and a preparation method to solve the above problem.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing a fully ceramic coated fuel, comprising preparing a mixed powder using matrix ceramic particles and dispersed fuel particles as raw materials; using the mixed powder as raw material, sequentially subjecting the mixed powder to a gel injection molding process and a sintering process to obtain a fully ceramic coated fuel; in the mixed powder, the content of the dispersed fuel particles is 40vol%-50vol%. A high content of dispersed fuel particles is conducive to increasing the uranium loading of the fuel element, thereby ensuring the service life of the fuel element and improving its economy, but an excessively high content of dispersed fuel particles will lead to difficulties in densification, low matrix densification, poor strength of the fuel element, high operating temperature, and reduced safety performance of the fuel element. In the mixed powder, the content of the dispersed fuel particles is more preferably 45vol%-50vol%.
[0008] To prepare the mixed powder, preferably planetary ball milling is used for mixing, the ball milling medium is anhydrous ethanol, the mixing balls are SiC balls (the matrix ceramic particles are SiC particles); the ball-to-material ratio is designed to be 1:10, the mixing time is 2h-4h, and then the mixed powder is poured out and dried in an air environment at 60°C for 2h to obtain a uniform mixed powder.
[0009] Further optionally, a sintering aid is added to the mixed powder.
[0010] Adding sintering aids during the powder mixing process is beneficial to the dispersion of the sintering aids. At the same time, the added sintering aids can increase the sintering density of the matrix material, which is beneficial to improving the strength and thermal conductivity of the fuel element.
[0011] Further optionally, the sintering aid is a mixture of Al2O3 and Y2O3; more preferably, Al2O3 and Y2O3 are mixed in a molar ratio of 1.5 to 3 as the sintering aid.
[0012] Other types of sintering aids include B4C, but the mixture of Al2O3 and Y2O3 can better improve the density at a lower sintering temperature.
[0013] Further optionally, the particle size of the matrix ceramic particles is ≤100 nm.
[0014] Further optionally, the gel casting process comprises:
[0015] S11: preparing ceramic slurry: mixing the mixed powder with a dispersant, an organic monomer, a solvent and a cross-linking agent to obtain a suspension; adjusting the pH value of the suspension to 8-10 by adding NaOH; adding a defoaming agent to remove bubbles to obtain a ceramic slurry;
[0016] S12: preparing a ceramic polymer colloid: adding a catalyst and an initiator to the ceramic slurry obtained in step S11, and reacting to prepare a ceramic polymer colloid;
[0017] S13: preparing a green body: drying, demoulding and debinding the ceramic polymer colloid obtained in step S12 to obtain a green body.
[0018] Preferably, the suspension is obtained by ball milling, for example, the ball milling mixing time is designed to be about 4 hours to 6 hours; before defoaming, a uniformly mixed ceramic slurry is obtained by sieving, and then a defoaming agent is added to the ceramic slurry for defoaming.
[0019] Further optionally, in step S11, the dosage of each material is: dispersant 0.1wt% to 0.5wt%, organic monomer 1wt% to 2wt%, solvent 40vol% to 60vol%, cross-linking agent 0.05wt% to 0.2wt%.
[0020] Preferably, the dispersant includes but is not limited to polyvinyl pyrrolidone, hydroxymethyl cellulose, methyl ammonium hydroxide, etc., the organic monomer includes but is not limited to N-hydroxymethyl acrylamide, agar and hydroxypropyl methyl cellulose, dimethyl acrylamide, the solvent includes but is not limited to tert-butyl alcohol, toluene, and the cross-linking agent includes but is not limited to methylene bis acrylamide, etc. .
[0021] Preferably, the defoaming agent includes but is not limited to n-butanol, and 0.3 ml to 0.5 ml is added. After adding the defoaming agent, vacuum defoaming is performed under a vacuum degree of less than 1 Pa to obtain the final ceramic slurry.
[0022] Further optionally, in step S12, the amount of catalyst added is 0.1wt% to 0.2wt%, the amount of initiator added is 0.1wt% to 0.3wt%; and the reaction temperature is 30°C to 60°C.
[0023] Preferably, the catalyst includes but is not limited to tetramethylethylenediamine, sodium hexametaphosphate, etc., and the initiator includes but is not limited to ammonium persulfate, seban, etc.
[0024] When preparing ceramic polymer colloid, a catalyst and an initiator (ammonium persulfate) are added to the ceramic slurry, stirred, and poured into the final mold. The mold is placed in an air environment at 30°C to 60°C, and a polymer colloid is obtained under the action of the catalyst and the initiator.
[0025] Preferably, in step S13, the ceramic polymer colloid can be first subjected to a low-temperature drying treatment (such as drying at 60°C for 12 hours), and then removed from the mold to obtain a green body with a certain strength; the green body is then subjected to a binder removal treatment in the air to burn out the organic matter therein, thereby obtaining a green body with a certain strength and a complex structure.
[0026] Further optionally, in step S13, the debinding process is method (i) or method (ii) or method (iii);
[0027] Method (i): placing the colloid in a muffle furnace for debinding, heating the temperature to 200°C to 250°C at a heating rate of 0.3°C / min to 1°C / min and keeping the temperature for 30min to 60min, then heating the temperature to 550°C to 650°C at a heating rate of 0.5°C / min to 1.5°C / min and keeping the temperature for 1h to 2h, then cooling the colloid with the furnace to obtain a green body;
[0028] Method (ii): placing the colloid in a tubular furnace, heating it to 200°C to 250°C at a heating rate of 0.3°C / min to 1°C / min and keeping it at that temperature for 30min to 60min, and at the same time, introducing air into one side of the tubular furnace at a gas flow rate of 200ml / min to 300ml / min, and then heating it to 550°C to 650°C at a heating rate of 0.5°C / min to 1.5°C / min and keeping it at that temperature for 1h to 2h, and then cooling it with the furnace to obtain a green body;
[0029] Method (iii): high-temperature organic matter is cracked in a vacuum furnace, the colloid is placed in the vacuum furnace, the temperature is increased to 500°C to 550°C at a heating rate of 0.5°C / min to 1.5°C / min and kept at this temperature for 1.5h to 3h, and then the furnace is cooled; the cracked green body is then placed in a muffle furnace, the temperature is increased to 600°C to 650°C at a heating rate of 0.5°C / min to 1.5°C / min and kept at this temperature for 2h to 4h to discharge the residual carbon after cracking, and then the green body is cooled to room temperature with the furnace to obtain the green body.
[0030] Further optionally, the sintering process includes: placing the green body prepared by the gel casting process in a gas pressure sintering furnace or a vacuum furnace for gas pressure or pressureless sintering.
[0031] The process parameters of gas pressure or pressureless sintering can be determined according to the structural dimensions of the high-density all-ceramic coated dispersed fuel element, the grain size of the ceramic matrix, the distribution state of TRISO particles, etc. This application is designed as follows:
[0032] Gas pressure sintering process: Sintering atmosphere: N2 or Ar, gas pressure: 3MPa-5MPa. The green body is heated from room temperature to 900℃~1000℃ at a heating rate of 10℃~20℃, and kept warm for 1h~2h; then heated to 1700℃~1800℃ at a heating rate of 10℃~15℃, and kept warm for 2h~4h.
[0033] Pressureless sintering process: Sintering atmosphere: N2 or Ar protection, vacuum degree: <1×10 -2Pa. The process flow is: directly heat the green body from room temperature to 1000℃-1100℃ at a rate of 10℃ / min-20℃ / min, and keep it at this temperature for 0.5-2h; then heat it to 2100℃ at a rate of 15℃ / min-20℃ / min, keep it at this temperature for 2-4h, and then cool it to room temperature with the furnace to complete the sintering.
[0034] After sintering, the sample surface can be treated, such as grinding and polishing. The dispersed fuel element after sintering is measured and polished to a standard size. Then, the dispersed fuel element is polished with sandpaper until there are no obvious scratches on the surface, thereby obtaining a finished fuel element.
[0035] The overall process of the preparation method of the fully ceramic coated fuel includes: ceramic slurry, ceramic polymer colloid, green body preparation, sintering treatment and surface treatment.
[0036] A fully ceramic coated fuel is prepared by using the above-mentioned method for preparing a fully ceramic coated fuel.
[0037] The present invention has the following advantages and beneficial effects:
[0038] Fully ceramic coated fuel has become an important candidate fuel for inherently safe high temperature reactors due to its high heat dissipation area, excellent irradiation stability, excellent fission product containment capacity, etc. However, ceramic materials are difficult to form, sinter and process, and the fuel prepared by existing processes has a simple structure and low matrix density, which cannot meet the design requirements of high temperature reactors.
[0039] The present invention solves the shortcomings of existing all-ceramic coated fuel preparation through a near-net forming / high temperature sintering method, including the difficulty in preparing complex structure fuel elements, the difficulty in densifying all-ceramic coated dispersed fuel, the inability to accurately control the size of the fuel-free zone, and the difficulty in controlling the TRISO particle distribution.
[0040] The present invention belongs to the preparation of near-net-shape all-ceramic dispersed fuel elements. By optimizing the viscosity and solid content of the ceramic slurry, a ceramic slurry suitable for gel injection molding is obtained; by adding a crosslinking agent, an initiator and a catalyst, a three-dimensional network polymer colloid is obtained; by injecting the colloid into a mold of a complex shape and demolding it, a green body of a corresponding shape is obtained; finally, a dispersed fuel element with a complex shape is obtained by debinding, high-temperature sintering and surface treatment. The preparation of highly dense dispersed fuel elements with complex shapes by the gel injection molding method can realize the near-net-shape molding and preparation of ceramic fuels with complex shapes, effectively reduce the processing amount of ceramic fuel elements, and solve the problem of preparing fuel elements with complex structures. The preparation of highly dense fully ceramic coated dispersed fuel elements by gel injection molding is suitable for the preparation of complex structural elements, has simple production process, low cost, and can realize large-scale industrial production. The prepared dispersed fuel elements have high density, high thermal conductivity, good toughness, and also have excellent thermal shock resistance, high-temperature oxidation and ablation resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0042] Figure 1 This is a morphology diagram of the ceramic polymer colloid of the present invention.
[0043] Figure 2 1 is the viscosity curve of the ceramic slurry with different solid content of the present invention.
[0044] Figure 3 This is a morphology diagram of the green body after debinding of the present invention.
[0045] Figure 4 This is a morphology diagram of the all-ceramic dispersed fuel element after sintering of the present invention; wherein: 1-TRISO particles; 2-SiC matrix.
[0046] Figure 5 This is a macroscopic structure diagram of the all-ceramic dispersed fuel element after sintering of the present invention. DETAILED DESCRIPTION
[0047] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0048] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details are not necessarily employed to practice the present invention. In other embodiments, in order to avoid obscuring the present invention, well-known structures, circuits, materials, or methods are not specifically described.
[0049] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any suitable combination and / or sub-combination. In addition, it will be appreciated by those of ordinary skill in the art that the figures provided herein are for illustrative purposes and that the figures are not necessarily drawn to scale. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0050] Example 1
[0051] This embodiment provides a ceramic slurry, and the specific steps are as follows:
[0052] Step 1: Prepare mixed powder
[0053] SiC particles (~100 nm), sintering aids and TRISO particles were mixed by ball milling.
[0054] Wherein, based on the amount of SiC particles, the amount of sintering aid is 6wt%; the sintering aid is a mixture of Al2O3:Y2O3, and the molar ratio is Al2O3:Y2O3=3:2.
[0055] The ball milling medium is anhydrous ethanol, the mixing balls are SiC balls, the ball-to-material ratio is 8:1, the mixing time is 8 h, and then the mixed powder is dried at 60°C to obtain a mixed powder.
[0056] Step 2: Prepare the ceramic slurry
[0057] The mixed powder obtained in step 1, 0.2 wt% polyvinyl pyrrolidone, 1 wt% N-hydroxymethyl acrylamide, 40 vol% tert-butyl alcohol and 0.1 wt% methylene bisacrylamide were ball-milled to obtain a suspension, and NaOH was added to adjust the pH to 10. The suspension was filtered through a 200-mesh sieve to obtain a suspension slurry.
[0058] The added amounts of polyvinyl pyrrolidone, N-hydroxymethyl acrylamide, tert-butyl alcohol and methylene bis acrylamide are all calculated based on the amount of the mixed powder.
[0059] According to the above method, the designed dosage of TRISO particles is 45 vol%, 50 vol%, 55 vol%, and 60 vol%, respectively.
[0060] The viscosity of the above ceramic slurry was tested:
[0061] Test method: The viscosity of the slurry is measured using a viscometer of Brookfield standard. The viscosity is measured using rotors 2 to 4 at a speed of 30 to 90 rpm.
[0062] The test results are as follows Figure 2 shown.
[0063] Example 2
[0064] This embodiment provides a fully ceramic coated fuel and a preparation method, which are specifically as follows:
[0065] Step 1: Prepare mixed powder
[0066] SiC particles (~100 nm), sintering aids and TRISO particles were mixed by ball milling.
[0067] Among them, based on the amount of SiC particles, the amount of sintering aid is 6wt%, and the amount of TRISO particles is 45vol%; the sintering aid is a mixture of Al2O3:Y2O3, and the molar ratio is Al2O3:Y2O3=3:2.
[0068] The ball milling medium is anhydrous ethanol, the mixing balls are SiC balls, the ball-to-material ratio is 8:1, the mixing time is 8 h, and then the mixed powder is dried at 60°C to obtain a mixed powder.
[0069] Step 2: Prepare the ceramic slurry
[0070] The mixed powder obtained in step 1, 0.2 wt% polyvinyl pyrrolidone, 1 wt% N-hydroxymethyl acrylamide, 40 vol% tert-butyl alcohol and 0.1 wt% methylene bisacrylamide were ball-milled to obtain a suspension, and NaOH was added to adjust the pH to 10. The suspension was filtered through a 200-mesh sieve to obtain a suspension slurry.
[0071] The added amounts of polyvinyl pyrrolidone, N-hydroxymethyl acrylamide, tert-butyl alcohol and methylene bis acrylamide are all calculated based on the amount of the mixed powder.
[0072] Step 3: Preparation of ceramic polymer colloid
[0073] Add 5 drops of n-butanol to the ceramic slurry prepared in step 2 and keep it in a vacuum environment of 0.5 Pa for 1 hour; then, add 0.1wt% tetramethylethylenediamine and 0.3wt% ammonium persulfate to the suspension, stir evenly and pour into a molding mold, and place the mold in an oven at 50°C for 8 hours, and demold to obtain a complex-shaped colloid.
[0074] Step 4: Prepare the green body
[0075] The colloid prepared in step 3 is placed in a muffle furnace for debinding, and the temperature is increased to 200°C at a heating rate of 0.5°C / min and kept at this temperature for 30 minutes, and then the temperature is increased to 550°C at a heating rate of 1°C / min and kept at this temperature for 1 hour, and then cooled with the furnace to obtain a green body with certain strength and complex structure.
[0076] Step 5: Sintering
[0077] A method for preparing a highly dense and complex structured all-ceramic coated dispersed fuel element by gas pressure sintering, wherein the specific preparation method is:
[0078] The green billet after debinding is placed in a graphite mold, and the graphite mold is placed in a gas pressure sintering furnace. The gas pressure furnace is first evacuated, and when the vacuum degree reaches below 0.1Pa, high-purity Ar gas is filled into the furnace to 3MPa, and other pressures are always kept at no more than 10Pa. The temperature is raised to 1000℃ at a heating rate of 10℃ / min, and kept at this temperature for 1h, and then raised to 1800℃ at a heating rate of 10℃ / min, and kept at this temperature for 4h, and then cooled with the furnace to obtain a dense dispersed fuel element.
[0079] Step 6: Surface Preparation
[0080] The sample sintered in step 5 was polished with 800, 1000, and 1200 mesh corundum water sandpaper until there were no obvious scratches on the surface to obtain a finished fuel element.
[0081] Example 3
[0082] The difference between this embodiment and embodiment 2 is that the process parameters for green body preparation and sintering in this embodiment are different, and the specific settings are as follows:
[0083] (a) When the debinding process is carried out using a tubular furnace, the debinding process is as follows:
[0084] The colloid is placed in a tubular furnace, and the temperature is increased to 200°C at a heating rate of 0.5°C / min and kept at this temperature for 30 minutes. At the same time, air is introduced into one side of the tubular furnace with a gas flow rate of 200 ml / min. The temperature is then increased to 550°C at a heating rate of 0.5°C / min and kept at this temperature for 1 hour. The colloid is then cooled with the furnace to obtain a green body with a certain strength and complex structure. The green body obtained by this method has a low content of organic matter and carbon impurities.
[0085] (b) When a two-step debinding process is used, the debinding process is as follows:
[0086] First, high-temperature organic matter is cracked in a vacuum furnace. The colloid is placed in a vacuum furnace and heated to 600°C at a heating rate of 1°C / min and kept warm for 2 hours, and then cooled with the furnace; the cracked green body is then placed in a muffle furnace and heated to 600°C at a heating rate of 1°C / min and kept warm for 2 hours to expel the residual carbon after cracking. The green body is then cooled to room temperature with the furnace to obtain a green body with certain strength and complex structure. The green body prepared by this method has low organic matter residue, which reduces the risk of cracking of the green body due to debinding.
[0087] (c) When the sintering method is pressureless sintering, the sintering process is:
[0088] The green body after debinding is placed in a mold and sintered without pressure. The sintering temperature is 2100℃, the sintering environment is vacuum sintering, the holding time is 6h, and the vacuum degree is <1×10 -2 Pa. The process flow is: heating to 1000℃ at 15℃ / min, keeping warm for 1h; heating to 2100℃ at 15℃ / min, keeping warm for 4h, and then cooling to room temperature with the furnace to obtain complex structure fuel elements. The preparation results are shown in Figure 5 The performance of the finished product in the above embodiment is tested.
[0089] Detection method:
[0090] Thermal conductivity is measured using a laser thermal conductivity meter: the temperature difference between the two sides of the sample is measured at different temperatures, and the thermal conductivity of the material is calculated.
[0091] The density is measured using the water displacement method: the sample is weighed in air and water, and then the sample density is calculated using Archimedes' principle.
[0092] The anti-ablation performance was measured by the oxyacetylene flame method. The mass loss at different times was measured: first, the original mass of the sample was weighed, and the sample was sprayed in the air with an oxyacetylene flame. The heat flux density of the oxyacetylene flame was 15 kW / cm. After the sample was cooled to room temperature after spraying for different times, the mass of the sample was weighed, and the ablation rate at different times was calculated.
[0093] The thermal shock resistance was tested by high temperature heating-water quenching: the sample was heated to 1100°C in a muffle furnace, then taken out and quickly placed in boiling water, and then the appearance quality of the sample was observed to obtain the thermal shock resistance of △T=1000°C.
[0094] The test results are shown in Table 1.
[0095]
[0096]
[0097] It can be seen from Table 1 that the method of the present invention can not only effectively overcome the problems of complicated steps in the preparation of existing all-ceramic coated dispersed fuel, difficulty in densification of complex structures, difficulty in molding complex structures, difficulty in preparing fuel-free zones, etc., but also has the advantages of simple production process, low cost, short production cycle, and suitability for industrial production; it also enables the prepared finished product to have the advantages of high thermal conductivity, high density, high thermal shock resistance, good ablation resistance, strong tolerance to fission products, etc., which can meet the requirements of high-temperature reactors.
[0098] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a fully ceramic coated fuel, characterized in that: The mixed powder is prepared by using the base ceramic particles and the dispersed fuel particles as raw materials; the mixed powder is processed by gel injection molding process and sintering process in sequence to obtain the fully ceramic coated fuel; in the mixed powder, the content of the dispersed fuel particles is 45vol%-50vol%; The mixed powder is prepared by the following method: the matrix ceramic particles and the dispersed fuel particles are mixed by planetary ball milling, the ball milling medium is anhydrous ethanol, and the mixing balls are SiC balls; the ball-to-material ratio is designed to be 1:10, the mixing time is 2h-4h, and then the mixed powder is poured out and dried in an air environment at 60°C for 2h to obtain a uniform mixed powder; The particle size of the matrix ceramic particles is ≤100nm; The gel casting process comprises: S11: preparing ceramic slurry: mixing the mixed powder with a dispersant, an organic monomer, a solvent and a cross-linking agent to obtain a suspension; adjusting the pH value of the suspension to 8-10 by adding NaOH; adding a defoaming agent to remove bubbles to obtain a ceramic slurry; S12: preparing a ceramic polymer colloid: adding a catalyst and an initiator to the ceramic slurry obtained in step S11, and reacting to prepare a ceramic polymer colloid; S13: preparing a green body: drying, demoulding and debinding the ceramic polymer colloid obtained in step S12 to obtain a green body; In step S11, the amount of each material is: dispersant 0.1wt%~0.5wt%, organic monomer 1wt%~2wt%, solvent 40vol%~60vol%, cross-linking agent 0.05wt%~0.2wt%; In step S12, the amount of catalyst added is 0.1wt%~0.2wt%, the amount of initiator added is 0.1wt%~0.3wt%; the reaction temperature is 30℃~60℃.
2. The method for preparing a fully ceramic coated fuel according to claim 1, characterized in that: A sintering aid is also added to the mixed powder.
3. The method for preparing a fully ceramic coated fuel according to claim 1, characterized in that: The sintering aid is a mixture of Al2O3 and Y2O3.
4. The method for preparing a fully ceramic coated fuel according to claim 1, characterized in that: In step S13, the debinding process is method (i) or method (ii) or method (iii); Method (i): The colloid is placed in a muffle furnace for debinding, and the temperature is raised to 200°C~250°C at a heating rate of 0.3°C / min~1°C / min and kept at this temperature for 30min~60min, and then the temperature is raised to 550°C~650°C at a heating rate of 0.5°C / min~1.5°C / min and kept at this temperature for 1h~2h, and then the colloid is cooled in the furnace to obtain a green body; Method (ii): Place the colloid in a tubular furnace, heat it to 200°C~250°C at a heating rate of 0.3°C / min~1°C / min and keep it at that temperature for 30min~60min, and at the same time, start to introduce air into one side of the tubular furnace, and the air flow rate is 200ml / min~300ml / min, then heat it to 550°C~650°C at a heating rate of 0.5°C / min~1.5°C / min and keep it at that temperature for 1h~2h, and then cool it in the furnace to obtain a green body; Method (iii): high-temperature organic matter is cracked in a vacuum furnace, the colloid is placed in a vacuum furnace, the temperature is increased to 500°C~550°C at a heating rate of 0.5°C / min~1.5°C / min and kept at this temperature for 1.5h~3h, and then the furnace is cooled; the cracked green body is then placed in a muffle furnace, the temperature is increased to 600°C~650°C at a heating rate of 0.5°C / min~1.5°C / min and kept at this temperature for 2h~4h to expel the residual carbon after cracking, and then the green body is cooled to room temperature with the furnace to obtain a green body.
5. The method for preparing a fully ceramic coated fuel according to claim 1, characterized in that: The sintering process includes: placing the green body prepared by the gel casting process in a gas pressure sintering furnace or a vacuum furnace for gas pressure or pressureless sintering treatment.
6. A fully ceramic coated fuel, characterized in that: The fuel is prepared by the method for preparing a fully ceramic coated fuel as described in any one of claims 1 to 5.
